Graft Versus Host Disease Associated with Immune Checkpoint Inhibitors: A Pharmacovigilance Study and Systematic Literature Review - Nguyen, Lee S.; Raia, Lisa; Lebrun-Vignes, Bénédicte; Salem, Joe-Elie (Frontiers in Pharmacology, 2021)
Background: In patients with allogenic hematopoietic stem cell transplantation (allo-HSCT), immune-checkpoint inhibitors (ICI) are used to treat malignancy recurrence. However, ICI are also associated with graft vs. host disease (GVHD). In this pharmacovigilance analysis, we aimed to characterize cases of GVHD associated with ICI, drawn from the World Health Organization pharmacovigilance database, VigiBase®, and from literature. Methods: We performed VigiBase® query of cases of GVHD associated with ICI. These cases were combined with those of literature, not reported in VigiBase®. The Bayesian estimate of disproportionality analysis, the information component, was considered significant if its 95% credibility interval lower bound was positive; denoting a significant association between GVHD and the suspected ICI. Time to onset between ICI and GVHD onset and subsequent mortality were assessed. Results: Disproportionality analysis yielded 93 cases of GVHD associated with ICI (61.8% men, median age 38 [interquartile range = 27; 50] years). Cases were mostly associated with nivolumab (53/93, 57.0%), pembrolizumab (23/93, 24.7%) and ipilimumab (12/93, 12.9%) monotherapies. GVHD events occurred after 1 [1; 5.5] injection of ICI, with a time to onset of 35 [IQR = 14; 176] days. Immediate subsequent mortality after GVHD was 24/93, 25.8%. There was no significant difference in mortality depending on the molecule (p = 0.41) or the combination regimen (combined vs. monotherapy, p = 0.60). Previous history of GVHD was present in 11/18, 61.1% in cases reported in literature. Conclusion: In this worldwide pharmacovigilance study, disproportionality yielded significant association between GVHD and ICI, with subsequent mortality of 25.8%. Previous history of GVHD was reported in more than half of cases. Clinicaltrials.gov identifier:NCT03492242